2019
DOI: 10.1128/cmr.00032-18
|View full text |Cite|
|
Sign up to set email alerts
|

A Laboratory Medicine Best Practices Systematic Review and Meta-analysis of Nucleic Acid Amplification Tests (NAATs) and Algorithms Including NAATs for the Diagnosis of Clostridioides ( Clostridium ) difficile in Adults

Abstract: SUMMARY The evidence base for the optimal laboratory diagnosis of Clostridioides (Clostridium) difficile in adults is currently unresolved due to the uncertain performance characteristics and various combinations of tests. This systematic review evaluates the diagnostic accuracy of laboratory testing algorithms that include nucleic acid amplification tests (NAATs) to detect the presence of C. difficile. The systematic review and meta-analysis included eligible studies (those that had PICO [population, interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 110 publications
(83 reference statements)
0
19
1
Order By: Relevance
“…In addition, the clinical practice guidelines for CDI in adults and children published by the Infectious Diseases Society of America and Society for Healthcare Epidemiology of America recommend testing by different approaches, such as multistep algorithms or NAAT, depending on the degree of clinical suspicion (17). Based on a systematic review and meta-analysis, the American Society of Microbiology also recommends different approaches, including NAAT-only testing, and algorithms that include GDH and NAAT or GDH, toxins, and NAAT (18). Although these recommendations stand to reason for detection of CDI in individual patients, our results challenge their utility for meaningful comparisons in surveillance studies and suggest that uniform definitions should be provided.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the clinical practice guidelines for CDI in adults and children published by the Infectious Diseases Society of America and Society for Healthcare Epidemiology of America recommend testing by different approaches, such as multistep algorithms or NAAT, depending on the degree of clinical suspicion (17). Based on a systematic review and meta-analysis, the American Society of Microbiology also recommends different approaches, including NAAT-only testing, and algorithms that include GDH and NAAT or GDH, toxins, and NAAT (18). Although these recommendations stand to reason for detection of CDI in individual patients, our results challenge their utility for meaningful comparisons in surveillance studies and suggest that uniform definitions should be provided.…”
Section: Discussionmentioning
confidence: 99%
“…In our institution, the actual average TAT per sample for the twostep algorithms was just 7.6-8.7 minutes more compared to each of the first step methods (QCC and VIDAS). The TAT of the two-step algorithm using the QCC assay (47.6 minutes) was similar to the one-step method using the Xpert assay (50 minutes) in our institution ( Table 3) the best practice for detecting the C. difficile toxin gene [16] as the widely-used Xpert assay demonstrated good sensitivity and specificity, comparable to CCNA or TC [10,24,32]. Therefore, the use of the Xpert assay as a reference method in this study should not have affected our findings.…”
Section: Discussionmentioning
confidence: 55%
“…However, they do not detect free toxins and therefore cannot differentiate between colonization and disease [24,25]. Rapid NAAT, as a single diagnostic method, could lead to decreases in the length of stay (approximately 2 days), days on empiric CDI treatment and isolation, and associated costs [17,26].…”
Section: Discussionmentioning
confidence: 99%
“…In the previous studies, the sensitivity between molecular assays and toxigenic culture have been reported as 82%-97% for the BD MAX Cdiff assay [7,10,15,28] and 83%-100% for the Xpert C. difficile [7,10,15,28,29]. Based on these results, we consider that the GENECUBE C. difficile assay has sufficient ability as a molecular assay.…”
Section: Discussionmentioning
confidence: 62%